Life and times of Edward Henry Pedris, national hero - Karunatilake, H. N. S. (s.n., 1978)
On E.H. Pedris, 1888-1915, Ceylonese aristocrat executed on the charges of treason during the 1915 communal disturbances in Sri Lanka.